mRNA extracted from frozen buffy coat samples stored long term in tubes with no RNA preservative shows promise for downstream sequencing analyses - Erik Bovinder Ylitalo; Linda Vidman; Sophia Harlid; Bethany Van Guelpen (PLoS ONE, 2025)
Transcriptomics is an important OMICs method that is often unavailable in biobank research. Frozen blood samples are routinely collected and stored in medical biobanks, but transcriptional studies have been limited due to technical difficulties of extracting high-quality RNA from blood frozen in standard tubes (without RNA preservatives). We aimed to determine whether biobanked buffy coat samples stored at -80°C for up to 23 years could be successfully used for mRNA sequencing. We used a CryoXtract CXT 350 to remove frozen sample cores, which were immersed in RNA preservative during thawing prior to RNA extraction. RNA sequencing was then performed on extractions from pooled samples as well as from 23 buffy coat samples from prospective colorectal cancer cases and 23 matched controls included in the population-based, prospective Northern Sweden Health and Disease Study (NSHDS). For all samples, two library preparation methods were used (Illumina TruSeq Stranded mRNA poly-A selection and Illumina Stranded Total RNA with Ribo-Zero Globin). RNA yields of over 1 µg were obtained from the majority of NSHDS samples (mean = 2.57 µg), and over 92% of samples had RIN values of ≥ 6, indicating suitability for downstream analyses. In conclusion, we developed a method for successfully extracting and sequencing high-quality mRNA from frozen buffy coat samples stored long term in tubes with no RNA preservative.